Faktor-Faktor yang Mempengaruhi Minat Berinvestasi di Pasar Modal - Ardyan Firdausi Mustoffa; LMS Kristiyanti (ITB AAS INDONESIA, 2023)
Investment is an important factor that influences the growth and economic development of a country. We as the young generation have an important role to play in increasing the growth and economic development of our country in a better direction, one of which is by participating in the success of government programs in terms of increasing the number of new investors among the younger generation, especially students. This study aims to analyze the effect of perception, understanding of investment and training on student investment interest in Ponorogo. The population in this study were active students at universities in Ponorogo with consideration of their status as active students for the 2021/2022 academic year at universities in Ponorogo where the college has an Investment Gallery of the Indonesia Stock Exchange, totaling 5399 students. The sampling technique was determined using the Slovin formula, from the calculation results obtained a sample of 100 student samples. The method of data collection is in the form of a questionnaire with a Likert measurement scale. The data analysis technique used is multiple linear regression analysis. The results showed that Perception has a significant positive effect on investment interest, meaning that the better one's perception of investment, the higher interest in investing in the capital market. Understanding of investment has a significant positive effect on investment interest, meaning that the better one's understanding of investment, the higher interest in investing in the capital market. Training has a significant positive effect on investment interest, meaning that the better the training, the more interest in investing. Perception, understanding of investment and training have a simultaneous (simultaneous) effect on investment interest. This means that the better the perception, understanding of investment and training, it will increase one's interest in investin”.